2021
DOI: 10.1016/j.isci.2021.103200
|View full text |Cite
|
Sign up to set email alerts
|

Miscell: An efficient self-supervised learning approach for dissecting single-cell transcriptome

Abstract: Summary We developed Miscell, a self-supervised learning approach with deep neural network as latent feature encoder for mining information from single-cell transcriptomes. We demonstrated the capability of Miscell with canonical single-cell analysis tasks including delineation of single-cell clusters and identification of cluster-specific marker genes. We evaluated Miscell along with three state-of-the-art methods on three heterogeneous datasets. Miscell achieved at least comparable or better perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…However, our benchmarking of SSL methods revealed the sensitivity to the choice of pre-training strategy. While contrastive methods have shown efficacy in other domains 41,43,44 and specialized in smaller scales in SCG 17,18,[20][21][22][23][24][25][26] , our study found that standard contrastive approaches did not yield as promising results for diverse, large-scale SCG tasks. This result highlights the challenges of applying these methods as generalizable pretext tasks for single-cell data.…”
Section: A Tailored Pre-training Strategy Leads To High Zero-shot Per...mentioning
confidence: 66%
“…However, our benchmarking of SSL methods revealed the sensitivity to the choice of pre-training strategy. While contrastive methods have shown efficacy in other domains 41,43,44 and specialized in smaller scales in SCG 17,18,[20][21][22][23][24][25][26] , our study found that standard contrastive approaches did not yield as promising results for diverse, large-scale SCG tasks. This result highlights the challenges of applying these methods as generalizable pretext tasks for single-cell data.…”
Section: A Tailored Pre-training Strategy Leads To High Zero-shot Per...mentioning
confidence: 66%
“…We identified 50 distinctive cell clusters (Fig. 1B ) that belong to immune cells and non-immune cells by Miscell 13 (see Methods section). The immune cells were primarily divided into T cells ( CD3D, CD3E ), B cells ( MS4A1, CD79A ), natural killer cells ( FGFBP2, KLRD1 ), monocytes, and macrophages ( LYZ, CD68, CD14 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression matrix was normalized by log2 transformation and scaled each gene by subtracting its mean and dividing with standard deviation. We extracted feature representations of single-cell using Miscell 13 . The gene expression signatures of single cells were captured by deep neural network.…”
Section: Methodsmentioning
confidence: 99%
“…Accompanied by the development of single-cell-based [177] and spatial-based [178] technologies that have been applied in molecular studies, numerous DL models are becoming more popular for computationally intensive analysis. To deal with the complexity of large genomics data, unsupervised deep clustering tools have been built for population structure identification [179] or cell population subtype annotation [180] , [181] , [182] , [183] . In addition, to process the complex structure of multi-omics data, graph neural network (GNN) models are increasingly popular in dataset integration [184] , biomedical classification [185] , prognosis prediction [186] , and so on.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%